Use of Fear Appeal in Work Safety Messages: An Experimental Study - Selin Türkel; Sema Misci Kip; Feyza Elif Yasdıman (Türkiye İletişim Araştırmaları Dergisi)
Persuasive communication messages are important in order to inform and motivate workers and encourage them to take work safety precautions. Fear appeals are broadly used to persuade individuals in public health and work safety communication messages. This experimental study compares attitudes, perceived ethicality, fear emotions, and behavioral intention of workers when exposed to a stimulus containing the threat of physical injury message, compared to a stimulus without such a message. Findings reveal statistically significant differences in terms of attitude toward the message and perceived ethicality when comparing two treatments. However, no significant differences emerged in fearful emotions and behavioral intention. Therefore, associations on work safety, governmental organizations, social marketers, and occupational safety specialists should be cautious about the effectiveness of threat of injury messages.